External Load in Elite Youth Soccer Players According to Age Category and Playing Position in Official International Matches - Aedo-Munoz, E (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background/Objectives: To compare the external load (EL) of elite youth soccer players during official international matches between age categories and playing positions. Methods: The sample consisted of 42 elite youth soccer players categorized by age categories, U-15, U-17 and U-20 and playing positions: central defender (CD); fullback (FB); midfielder (MF); wide attacker (WA) and striker (ST). The Vector X7 (Catapult Sports) device was used for collecting the following EL variables: total distance traveled (TD), player load (PL) and distance traveled per velocity band 0 to 7 km/h (D7); 7 to 13 km/h (D13); 13 to 19 km/h (D19); 19 to 23 km/h (D23) and >23 km/h (HSR). Linear mixed-effect models were applied to analyze the differences. Results: Large differences were found between positions (p < 0.01) in TD (η2p = 0.48), PL (η2p = 0.30), D19 (η2p = 0.44), D23 (η2p = 0.68) and HSR (η2p = 0.53). Large differences were found according to category between U-15 and U-17 in TD (p = 0.006 and η2p = 0.25) and D13 (p = 0.003 and η2p = 0.27). Large interaction effects were found in DT (p = 0.014 and η2p = 0.44) and D23 (p = 0.002 and η2p = 0.51). Conclusions: This study concludes that there are differences in EL in official matches in elite youth players between age categories and playing position. These differences can be applied in practice to design individualized training by playing position and to monitor EL during microcycles. © 2025 by the authors.